PERSEPSI TOKOH ADAT DAN TENTANG TRADISI UPACARA ADAT KEMATIAN DALAM SISTEM KEKERABATAN DALIHAN NATOLU DI KECAMATAN PAYUNG SEKAKI KELURAHAN LABUH BARU BARAT PEKANBARU - Hotma Hasugian; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the perception of usual leaders. Implementation of the tradition of death ceremonies consisting of 3 levels of usual death of batak, namely matua sari, saur matua and mauli bulung, whether it remains good or there A shift has occurred in traditional ceremonies. Namely the role of Dalihan Natolu in the implementation of adat, the use of meat from slaughtered / farmed animals, used ulos, the fees used in large numbers in traditional ceremonies are reasonable or not. Regarding the research population, 34 figures and those who are aware of adat. by using qualitative approach techniques, (Sugiyono, 2015). Sugiyono, (2015) said that "said this qualitative study is a study that results in the form of written and oral words from the observed people". This technique for collecting data sets used is observation, questionnaires and interviews. When analyzing the data using qualitative descriptive data from Sugiyono (2015), namely the formula P = F / N X 100%. The results of this study indicate that the perception of students of Riau University about the functions of political parties in Indonesia is seen from the percentage of 90 respondents who are 3.27% for the bad category, 34.69% for the bad category , 52.72% for the good category and 9.32% for the excellent category. The results of testing hypotheses can then be accepted.Key Words : Comparative, Social Care